A Study on water quality of Galing River,Kuantan - Hajjar, Husein (2016)
Water pollution has a harmful effect on all living things that used and lives in it, and Galing River is one of the river in Kuantan that has been severely polluted. The rapid development in the catchment area of the Galing River has exposed it to various pressures that resulted in the occurrence of events such as flooding, contamination / deterioration of water quality, lack of water resources, erosion in riverbank / riverbed, squatters, and legislation in managing the river. The aim of the study was to determine the water quality status of the Galing River and classified based on Water Quality Index (WQI) and National Water Quality Standard (NWQS), Malaysia. To achieve the objectives, 9 times water samples were collected in the month from September to November 2015. Physical, chemical and biological parameters were analyzed using standard methods. The WQI was calculated using DOE-WQI based on the concentration of DO, BOD, COD, TSS, pH and NH3-N. Other parameters that had been considered in this study were temperature, conductivity, selected heavy metals, total coliform and E.coli. Based on results, Station 1 was categorized as Class II (clean), Station 2 was under Class III (slightly polluted) while Station 3 was classified as Class IV (polluted). The lowest WQI value was 48.07 and the highest value was 84.51. It was mainly because the low concentration of DO and high concentration of BOD, COD and NH3-N due to the surrounding activities such as industrial, municipal waste and effluent from residential areas. The results indicate that the Galing River is clean based on NWQS, Malaysia at Station 1 which can be used as water supply and only needed a conventional treatment. Overall, water can be supplied from the Galing River but required extensive treatment. Finally the monthly monitoring is necessary to improve the quality of the Galing River.